Pengembangan Sistem Notifikasi Pada LMS Moodle Melalui Penerapan Multi Channel Access Dengan Pemanfaatan Webhook - Putra, Rio Juniyantara; Wiharta, Dewa Made; Sastra, Nyoman Putra Putra (Majalah Ilmiah Teknologi Elektro; Vol 22 No 2 (2023): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i02.P08, 2023)
The development of Moodle E-Learning technology has progressed rapidly to meet and support diverse learning needs. In the learning process of Moodle E-Learning, various activities are involved, such as creating assignments, providing assessments, and other activities. However, these processes have limitations, such as students not being immediately aware when assignments are created or when assessments are given. This often leads to delays in completing tasks as students wait for manual notifications from their instructors. Additionally, students sometimes forget to regularly check Moodle for updates. To address these shortcomings, the researcher aims to develop a MCA notification BOT application that integrates Moodle with social media platforms like Line and Telegram using webhooks. The purpose of this system is to help students receive real-time information about assignments and assessments provided on Moodle by their instructors. The testing results demonstrate that the implemented features function well and align with the intended design.